On the origin of the contractile force in skeletal muscle. - Harrington, W F (1979)
Analysis of the early tension responses after abrupt step changes in the length of isometrically contracting skeletal muscle shows that the magnitude of the recovery tension (T2) and the time dependence of this process at various step displacements give a good correlation with the behavior expected for a helix-coil transition in the subfragment-2 (S-2) region of myosin. The "instantaneous" tension response (to T1) after the step change in length appears to have its origin in compliance within the coil region of S-2, which is formed through helix melting at the moment of force generation.